Generalized Elastic Lateral-Torsional Buckling of Steel Beams - Glauz, Robert; Schafer, Benjamin (Engineering Journal, 2025)
A concise review is provided of the classical elastic lateral-torsional buckling moment for steel beams as utilized in the AISC Specification (2022). Rather than make assumptions regarding the cross-section properties, the derivation is provided in its general form for an arbitrary steel beam—that is, one that may be asymmetric and may include any manner of varying geometry, thickness, or cross-section shape. The cross-section properties that underpin the calculation are fully detailed. The assumptions that are inherent in the classical derivations (no shear, no cross-section distortion, etc.) are also fully detailed. The manner in which the generalized lateral-torsional buckling formula may be simplified for particular sections (e.g., a singly symmetric channel) with no loss of accuracy is explained. Adaptations and approximations utilized in the 2022 edition of the AISC Specification for elastic lateral-torsional buckling moment of specific sections (e.g., mono-symmetric I-section, angles, etc.) are assessed against the actual elastic solution, and the accuracy and clarity of the assumptions utilized are evaluated. The generalized formula, consistent with current assumptions but applicable to all structural steel cross sections, is recommended for future reference in the main body of the AISC Specification.